2020
DOI: 10.1111/ijlh.13334
|View full text |Cite
|
Sign up to set email alerts
|

Lupus anticoagulant in patients with COVID‐19

Abstract: Patients with COVID-19 are at increased risk of thromboembolism. In a recent study of 184 patients with COVID-19, there was a cumulative incidence of venous thromboembolism of 27% and arterial thrombotic events of 3.7%. 1 Abnormal coagulation parameters, particularly elevated D-dimer and fibrinogen, have been shown to be associated with poor prognosis in these patients, 2 and anticoagulation is associated with decreased mortality in severe COVID-19. 3 Antiphospholipid antibodies, mainly lupus anticoagulant (LA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 8 publications
2
15
0
Order By: Relevance
“…As demonstrated in Table 2, the presence of antiphospholipid antibodies (aPL) has been observed in COVID-19 patients around the world (18)(19)(20)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). The association between aPL and disease severity was shown in three studies (39,54,56), but not in another study (46).…”
Section: Antiphospholipid Antibody Syndrome (Aps)mentioning
confidence: 98%
“…As demonstrated in Table 2, the presence of antiphospholipid antibodies (aPL) has been observed in COVID-19 patients around the world (18)(19)(20)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). The association between aPL and disease severity was shown in three studies (39,54,56), but not in another study (46).…”
Section: Antiphospholipid Antibody Syndrome (Aps)mentioning
confidence: 98%
“…[103][104][105][106] The presence of IgG or IgM anti-cardiolipin and anti-beta2-glycoprotein I antibodies in patients with COVID-19 seems to be less prevalent and more variable across different studies, ranging from 0% to D 1 3 6 X X13%. 104,105,107,108 Interestingly, there has been conflicting evidence on how well the presence of antiphospholipid antibodies correlate with clinically significant thrombotic episodes, with various initial studies suggesting that these represent innocent bystanders instead of pathogenic antibodies. [103][104][105][107][108][109][110][111] However, a recent study has demonstrated a potential pathogenic role of antiphospholipid antibodies in severe COVID-19.…”
Section: Convergent Immunopathogenic Mechanisms Of Covid-19 and Slementioning
confidence: 99%
“…104,105,107,108 Interestingly, there has been conflicting evidence on how well the presence of antiphospholipid antibodies correlate with clinically significant thrombotic episodes, with various initial studies suggesting that these represent innocent bystanders instead of pathogenic antibodies. [103][104][105][107][108][109][110][111] However, a recent study has demonstrated a potential pathogenic role of antiphospholipid antibodies in severe COVID-19. This cross-sectional study showed that 50% of hospitalized patients with COVID-19 had antiphospholipid antibodies, and higher titers were associated with elevated circulating NET markers and a more severe COVID-19 course.…”
Section: Convergent Immunopathogenic Mechanisms Of Covid-19 and Slementioning
confidence: 99%
See 1 more Smart Citation
“…53,71,72 It is important to note that CRP is also highly elevated in patients with COVID-19, including those with reported LA. 51,55,56,58,59,61,62,[64][65][66][67] Interestingly, however, most researchers reporting on LA in COVID-19 did not mention CRP, nor report data on this biomarker. In some cases, these data may have possibly been reported elsewhere, and in other casesmaynothavebeengatheredorevenconsidered.Offurther interest, even when investigated or reported, CRP was not always contemplated by the researchers as a potential confounder for LA identification.…”
Section: C-reactive Proteinmentioning
confidence: 99%